Commentary on Highly Restrained Welded Connections - American Institute of Steel Construction (Engineering Journal, 1973)
The American Institute of Steel Construction, recognizing the need for dissemination of information to designers and fabricator-erectors on potential problems encountered in highly restrained welded connections, created a Task Force with the assigned responsibility of reviewing published relevant technical literature to develop a discussion of the factors and mechanisms that would be useful to the design profession and construction industry. The report of this Task Force of the AISC Committee on Fabricating Operations and Quality Standards resulted in this document, which is a "State of the Art" presentation reflecting information presently available. With regard to the points raised in this commentary concerning highly restrained welded connections, it is emphasized that for the great majority of welded connections the conditions which provide the potential for lamellar tearing or other distress do not exist. It is only in a limited number of connections in welded structures that critical requisite conditions may precipitate a lamellar tear. The purpose of this paper is to present information which will be an aid in minimizing the occurrence of such conditions.